Mni Sota Makoce : The Land of the Dakota - Westerman, Gwen; White, Bruce M., 1951- (Book collections on Project MUSE., 2012)
Much of the focus on the Dakota people in Minnesota rests on the tragic events of the 1862 U.S.-Dakota War and the resulting exile that sent the majority of the Dakota to prisons and reservations beyond the state's boundaries. But the true depth of the devastation of removal cannot be understood without a closer examination of the history of the Dakota people and their deep cultural connection to the land that is Minnesota. Drawing on oral history interviews, archival work, and painstaking comparisons of Dakota, French, and English sources, Mni Sota Makoce tells the detailed history of the Dakota people in their traditional homelands for at least hundreds of years prior to exile. "Minnesota" is derived from the Dakota phrase Mni Sota Makoce, Land Where the Waters Reflect the Clouds -- and the people's roots here remain strong. Authors Gwen Westerman and Bruce White examine narratives of the people's origins, their associations with the land, and the seasonal round through key players and place names. They consider Dakota interactions with Europeans and offer an in-depth "reading between the lines" of historical documents -- some of them virtually unknown -- and treaties made with the United States, uncovering misunderstandings and outright deceptions that helped lead to war in 1862.